The Response of Earth's Electron Radiation Belts to Geomagnetic Storms: Statistics From the Van Allen Probes Era Including Effects From Different Storm Drivers - Turner, D. L.; Kilpua, E. K. J.; Hietala, H.; Claudepierre, S. G.; O'Brien, T. P.; Fennell, J. F.; Blake, J. B.; Jaynes, A. N.; Kanekal, S.; Baker, D. N.; Spence, H. E.; Ripoll, J.‐F.; et al. (Journal of geophysical research. Space physics, 2019)
A statistical study was conducted of Earth's radiation belt electron response to geomagnetic storms using NASA's Van Allen Probes mission. Data for electrons with energies ranging from 30 keV to 6.3 MeV were included and examined as a function of L‐shell, energy, and epoch time during 110 storms with SYM‐H ≤−50 nT during September 2012 to September 2017 (inclusive). The radiation belt response revealed clear energy and L‐shell dependencies, with tens of keV electrons enhanced at all L‐shells (2.5 ≤ L ≤ 6) in all storms during the storm commencement and main phase and then quickly decaying away during the early recovery phase, low hundreds of keV electrons enhanced at lower L‐shells (~3 ≤ L ≤ ~4) in upward of 90% of all storms and then decaying gradually during the recovery phase, and relativistic electrons throughout the outer belt showing main phase dropouts with subsequent and generally unpredictable levels of replenishment during the recovery phase. Compared to prestorm levels, electrons with energies >1 MeV also revealed a marked increase in likelihood of a depletion at all L‐shells through the outer belt (3.5 ≤ L ≤ 6). Additional statistics were compiled revealing the storm time morphology of the radiation belts, confirming the aforementioned qualitative behavior. Considering storm drivers in the solar wind: storms driven by coronal mass ejection (CME) shocks/sheaths and CME ejecta only are most likely to result in a depletion of >1‐MeV electrons throughout the outer belt, while storms driven by full CMEs and stream interaction regions are most likely to produce an enhancement of MeV electrons at lower (L < ~5) and higher (L > ~4.5) L‐shells, respectively. CME sheaths intriguingly result in a distinct enhancement of ~1‐MeV electrons around L~5.5, and on average, CME sheaths and stream interaction regions result in double outer belt structures. Key Points A statistical model of electron radiation belt response to storms as a function of energy and L‐shell is developed Storm‐time morphology of the electron radiation belts is qualitatively predictable Results are better organized when the solar wind drivers of storms are identified